A new species of hermit crab of the genus Pagurus Fabricius, 1775 (Crustacea: Anomura: Paguridae) from north-western Africa - Almón, Bruno; Cuesta, Jose A.; García-Raso, J. Enrique (Zootaxa, 2022)
One male and two female specimens of an undescribed species of the heterogeneous hermit crab genus Pagurus Fabricius, 1775, were found during the study of the collections of the Oceanographic Institute of Cádiz, containing specimens from African and European coasts collected during the scientific cruises carried out between in years 2008–2013. The new species is named Pagurus pectinidactylus n. sp., in reference to the presence of a well-developed toothless pectinate masticatory border in the dactylus of the left cheliped, composed by a row of tightly placed bristles forming a brush-like structure. The new species is compared to morphologically similar congeners, especially those that are genetically closest. Molecular phylogenetic analyses support the morphological delimitation, with P. pectinidactylus n. sp. forming a separate clade, more closely related to a group of South African species belonging to the Pagurus anachoretus group.